Populations across bird species distribution ranges respond differently to habitat loss and fragmentation: implications for conservation strategies - Hasui, Érica; Martensen, Alexandre Camargo; Uezu, Alexandre; Pimentel, Rafael Guerra; Ramos, Flavio Nunes; Ribeiro, Milton Cezar [UNESP]; Metzger, Jean Paul (Elsevier, 2024)
Conservation strategies often assume uniform response to habitat loss and fragmentation among species. We investigated whether bird species' responses to habitat changes vary based on their distribution range and local environmental suitability. Additionally, we explored associations between sensitivity responses and species traits, like dispersal ability, habitat specialization, and distribution range size. Our study focused on the Brazilian Atlantic Forest, encompassing 179 landscape sites and 81 bird species. Using additive and interactive relationships and used principal component analysis to correlate species traits with sensitivity patterns. We found four distinct patterns of population sensitivity patterns: no effect of geographical range or environmental suitability (21% of the species), higher sensitivity at the geographical edges or low suitability (14%), lower sensitivity in core or better areas (11%) or both extremes responding similarly (11%), with species showing no response to landscape changes (43%). Biogeographic and landscape factors interactively influenced population abundance, resulting in antagonistic or synergistic effects. Population responses to habitat loss and fragmentation varied based on range position or environmental suitability but weren't consistently explained by species traits. Given these nuanced results, conservationists must refrain from generalizing species sensitivity without accounting for distribution range position and environmental suitability. To ensure the long-term survival of biodiversity, conservation efforts should be tailored to each species' specific needs, taking into account their spatial position and the synergistic or antagonistic effects of environmental stressors. Such targeted conservation efforts will be crucial in mitigating the impacts of habitat loss and fragmentation on bird populations within the Brazilian Atlantic Forest.
Keywords: Abundant-center model; Aves; Bird; Habitat suitability; Landscape; Niche modeling